Exploration of Constructive Learning through Science Curriculum at Primary Level - Alia Aslam، Tahira Bibi (JCTE, 2023)
Constructivist education embodies the ideals of cognitive conflict and resolution through intervention. Science is the study of physical environment through observation and personal experience.